Detection of thyroglobulin in fine-needle aspiration for diagnosis of metastatic lateral cervical lymph nodes in papillary thyroid carcinoma: A retrospective study - Wang, Yuxuan; Duan, Yuansheng; Li, Hong; Yue, Kai; Liu, Jin; Lai, Qingchuan; Zhou, Mengqian; Ye, Beibei; Wu, Yue; Zhu, Jiajia; Chen, Peng; Jing, Chao; et al. (Frontiers in Oncology, 2022)
Objective: We analysed the diagnostic performance of thyroglobulin in fine-needle aspiration (FNA-Tg) in the suspicious lateral cervical lymph nodes (CLNs) in patients with papillary thyroid cancer (PTC), proposed the best cutoff value and discussed the factors that may affect the diagnostic value of FNA-Tg. Methods: In the present study, a retrospective analysis of 403 patients with PTC with 448 suspected lateral CLNs metastasis from October 2019 to May 2021 was performed. The cutoff value according to the receiver operating characteristic (ROC) curve was determined, and the Wilcoxon rank-sum test was used to evaluate the correlation between FNA-Tg and factors. Results: According to the ROC curve, the cutoff value of FNA-Tg was 3.69 ng/ml (sensitivity, 92.48%; specificity, 75.00%). Patients who underwent total thyroidectomy were excluded. Compared with US and FNAC, the diagnostic performance of FNA-Tg was the greatest, especially for small CLNs (diameter ≤ 1 cm), cystic CLNs, and patients with Hashimoto’s thyroiditis (HT). Moreover, FNA-Tg levels were correlated with the presence of HT (p = 0.003), the anti-thyroglobulin antibody (Tg-Ab) (p < 0.001), the ratio of metastatic lateral CLNs (p = 0.004) and Tg assay kits (p < 0.001). Conclusions: FNA-Tg measurement is sensitive enough for diagnosing lateral CLN metastases from PTC, but its diagnostic value is compromised by a number of factors.